Analysis of common barriers to rural patients utilizing hospice and palliative care services: An integrated literature review. Issue 6 (30th May 2017) - Tedder, Tara; Elliott, Lydia; Lewis, Karen
Abstract: Background and purpose: The aim of this literature review is to explore barriers and potential solutions related to hospice (HC) and palliative care (PC) services among rural residents. Although the healthcare system is continually advancing, healthcare providers may not be optimizing HC and PC referrals for the growing rural population who underutilize these services. Suggested methods to close the utilization gap between HC and PC services among rural patients appear feasible, but universal effectiveness cannot be determined. Methods: An integrative literature review was conducted to evaluate diverse sources of literature. An electronic literature search was carried out using databases MEDLINE, CINAHL, Cochrane, PsycINFO, and Pubmed. The search was limited to English only, full text, peer reviewed, and published between 2010 and 2016. Search terms included rural, hospice, palliative, care access, and barriers. Conclusion: There are several barriers that interrelate to decreased utilization of PC and HC for rural populations and there are many options for overcoming them to equalize care. Implications for practice: Although advances to the general healthcare system are expediently rising, the rural patient population seems to fall short of these important life‐changing services, especially in the realm of PC/HC. Beginning in primary care, this patient population can be affected and included in a positive manner.